Property Changes of the Traditional Beef Curry Product ‘Gulai-Besar’ Packed in Retort Pouch during Storaging - Tayeh, Nutchanet; Ayukhen, Angsana; Louhasakul, Yasmi (Journal of Food Health and Bioenvironmental Science, 2023)
The main objective of this study was to figure the changes of physicochemical as well as the sensory properties of the traditional beef curry product ‘GulaiBasar’ packed in retort pouch during storage up to 9 months. Gulai-Besar was prepared according to the local recipe. It was packed in retort pouch (250 g) and processed in a retort at 116°C for 26 minutes and the F0 Value of 5.77. The retort processed Gulai-Besar was analyzed for microbiological, sensory and chemical characteristics under refrigerated (4±2°C), ambient temperature (30±2°C), and accelerated temperature (55±2°C) for 9 months. All the processed samples showed an increasing trend of peroxide value (PV), free fatty acid (FFA), ash and sensory attributes while a decreasing trend of pH, protein and moisture content were showed. The fat slightly increased during storage time in all conditions. However, mesophile aerobes and anaerobes were absent and the samples were safe with acceptable sensory attributes entire storage period. The shelf life study indicated that the products were well acceptable up to 9 months based on the assessment of physicochemical, microbiological and sensory attributes. This implies that it is feasible to produce Gulai-Besar to commercial scale.